(untitled) (Revista Brasileira Multidisciplinar, 2024)
Propolis is produced by bees from different botanical sources and is expanding consumption in the form of an extract. During the COVID-19 pandemic, propolis extract consumption habits may have changed, due to a product culturally advertised as a natural remedy. For data collection, the Survey method was used, a questionnaire consisting of 17 questions and 227 respondents. The data were exported to an Excel spreadsheet, where a distribution analysis of the qualitative and quantitative variables of each selected question took place. It was found that 64.3% women and 35.7% men, predominantly aged between 20 and 29 years, heterogeneous public in terms of education and income, and 86.4% of the participants were from the state of São Paulo. As for the level of education, 39.3% of the participants were studying or had a graduate degree; 56% were attending or had completed graduation and 4.7% had secondary or elementary education. About 185 (81.49%) of the 227 participants, 185 (81.49%) use propolis when they are sick, mainly for sore throat (23.9%). Other reasons for consuming propolis were: COVID-19, flu and cold, immunity and sinusitis. About 21.1% of participants increased their consumption of propolis extract during the pandemic.